1994
DOI: 10.2307/1131361
|View full text |Cite
|
Sign up to set email alerts
|

Transfer in Young Children's Understanding of Spatial Representations

Abstract: The creative and flexible use of symbols is a unique human ability. In order to use a symbol, one must understand the basic relation between the symbol and what it represents. How do young children come to appreciate such relations? One possibility is that insight into one symbolic relation helps children appreciate different ones. The 3 studies presented here support this possibility. In Experiments 1 and 2, both 2.5- and 3.0-year-old children showed transfer from an easy task that required appreciation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
57
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 0 publications
8
57
0
4
Order By: Relevance
“…Further research is needed to establish to what extent this core knowledge is shared with other animal species (14,15) and whether it is available even in infancy or is acquired progressively during the first years of life (4, 10, 16-18). There is little doubt that geometrical knowledge can be substantially enriched by cultural inventions such as maps (19), mathematical tools (3,4,6), or the geometrical terms of language (18,(20)(21)(22)(23)(24)(25). Beneath this fringe of cultural variability, however, the spontaneous understanding of geometrical concepts and maps by this remote human community provides evidence that core geometrical knowledge, like basic arithmetic (7,26), is a universal constituent of the human mind (11).…”
Section: Reportsmentioning
confidence: 99%
“…Further research is needed to establish to what extent this core knowledge is shared with other animal species (14,15) and whether it is available even in infancy or is acquired progressively during the first years of life (4, 10, 16-18). There is little doubt that geometrical knowledge can be substantially enriched by cultural inventions such as maps (19), mathematical tools (3,4,6), or the geometrical terms of language (18,(20)(21)(22)(23)(24)(25). Beneath this fringe of cultural variability, however, the spontaneous understanding of geometrical concepts and maps by this remote human community provides evidence that core geometrical knowledge, like basic arithmetic (7,26), is a universal constituent of the human mind (11).…”
Section: Reportsmentioning
confidence: 99%
“…One factor that has been hypothesized to make an important contribution to children's increasing ability to achieve representational insight with novel symbolic artifacts is their prior experience with symbols (DeLoache, 1995, 2002; Marzolf & DeLoache, 1994). It has been proposed that children's cumulative experience with a variety of symbolic artifacts (pictures, picture books, video, replica toys, and so on) contributes to the development of symbolic sensitivity—a general readiness or proclivity to interpret a novel entity primarily in terms of something other than itself (DeLoache, 1995, 2002).…”
Section: Summary Of Performance In Scale Model Tasks As a Function mentioning
confidence: 99%
“…However, DeLoache and colleagues have identified a number of conditions and parameters that moderate children’s symbol performance, including explicit verbal instructions on the task (DeLoache, 1989) and the degree of iconicity between the model and the room (DeLoache et al, 1991; Ganea et al, 2009). An additional finding from this lab is that, for their standard search tasks, children consistently show an appreciation of 2D symbols before 3D symbols (DeLoache, 1987, 1991; DeLoache & Burns, 1994; Marzolf & DeLoache, 1994). …”
mentioning
confidence: 76%
“…First DeLoache and colleagues consistently have found that children’s ability to use symbols to guide their search for hidden objects undergoes rapid development between ages 2.5- and 3-years (DeLoache, 1987, 1991; DeLoache & Burns, 1994; Marzolf & DeLoache, 1994). Our findings identify a later age of competence in using symbols to demonstrate body touch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation